Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1161/jaha.120.019211
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for Heart Failure Among Patients With Diabetes Mellitus and Reduced Kidney Function Treated With Metformin Versus Sulfonylureas: A Retrospective Cohort Study

Abstract: Background Metformin and sulfonylurea are commonly prescribed oral medications for type 2 diabetes mellitus. The association of metformin and sulfonylureas on heart failure outcomes in patients with reduced estimated glomerular filtration rate remains poorly understood. Methods and Results This retrospective cohort combined data from National Veterans Health Administration, Medicare, Medicaid, and the National Death Index. New users of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Metformin. Metformin remains the most widely used of oral medications for T2D (1,155). Metformin improves insulin sensitivity, is typically weight neutral or may induce weight loss, effectively prevents diabetes development, and is affordable given its low costs (156).…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin. Metformin remains the most widely used of oral medications for T2D (1,155). Metformin improves insulin sensitivity, is typically weight neutral or may induce weight loss, effectively prevents diabetes development, and is affordable given its low costs (156).…”
Section: Key Pointsmentioning
confidence: 99%
“…However, in contrast to the safety and possible benefits of metformin, several observational studies have suggested that sulfonylurea therapy may be associated with increased risk of HF events compared with metformin or with other agents (2). Evidence from a large retrospective cohort, with data combined from the National Veterans Health Administration, Medicare, Medicaid, and the National Death Index, that included 24,685 metformin users and 24,805 sulfonylurea users with reduced kidney function (median age 70 years, estimated glomerular filtration rate 55.8 mL/min/1.73 m 2 ) showed significantly fewer HF hospitalizations per 1,000 person-years for metformin compared with sulfonylurea users (155). In addition, in a most recent comparative effectiveness study with analysis of data from 128,293 participants with T2D in the U.S. Department of Veterans Affairs, of whom 23,870 received an SGLT2i and 104,423 received a sulfonylurea, it was reported that SGLT2i treatment was associated with a reduced risk of all-cause mortality compared with sulfonylureas (162).…”
Section: Key Pointsmentioning
confidence: 99%
“…Metformin reduced the risk of admission for HF compared to thiazolidinediones, sulfonylureas, or other non-metformin contemporary regimens, and once again versus sulfonylureas in T2DM patients who persisted in the use of biguanide despite reduced kidney function [ 13 , 14 , 181 , 198 , 205 ]. This benefit was confirmed by systematic reviews and meta-analyses [ 189 , 190 , 191 , 196 ].…”
Section: Effects Of Metformin On Adverse Consequences Of Hf In Clinical Studiesmentioning
confidence: 99%
“…diabetes published since the appearance of this meta-analysis (2017) support its findings, with reduced mortality versus non-metformin treatment [36,37], reduced hospitalisation versus non-metformin treatment [38], or reduced hospitalisation versus sulfonylurea treatment in patients with comorbid CKD [39]. Another cohort study suggested that metformin versus sulfonylurea as initial pharmacologic antihyperglycaemic treatment was associated with a lower risk of hospitalisation for HF in a population with a low prevalence of HF at baseline [40].…”
Section: Clinical Outcomes Following Metformin Treatment In People Wi...mentioning
confidence: 86%